2015
DOI: 10.1128/aac.00498-15
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Ceftaroline in Normal Body Weight and Obese (Classes I, II, and III) Healthy Adult Subjects

Abstract: The pharmacokinetic profile of ceftaroline has not been well characterized in obese adults. The purpose of this study was to evaluate the pharmacokinetics of ceftaroline in 32 healthy adult volunteers aged 18 to 50 years in the normal, overweight, and obese body size ranges. Subjects were evenly assigned to 1 of 4 groups based on their body mass index (BMI) and total body weight (TBW) (ranges, 22.1 to 63.5 kg/m 2 and 50.1 to 179.5 kg, respectively). Subjects in the lower-TBW groups were matched by age, sex, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 28 publications
3
30
1
Order By: Relevance
“…As far as plasma is concerned, Table 2 shows that the values of the key PK parameters of CPT after administration q12h (i.e., the currently recommended dosing regimen) were in line with the values from the recent literature (21,22). In comparison, administration of CPT-F q8h produced significantly higher AUC 0 -24 and, more importantly, fT MIC values.…”
Section: Discussionsupporting
confidence: 72%
“…As far as plasma is concerned, Table 2 shows that the values of the key PK parameters of CPT after administration q12h (i.e., the currently recommended dosing regimen) were in line with the values from the recent literature (21,22). In comparison, administration of CPT-F q8h produced significantly higher AUC 0 -24 and, more importantly, fT MIC values.…”
Section: Discussionsupporting
confidence: 72%
“…A phase I PK study of ceftaroline 600 mg every 12 hours showed that while Vd and Cl were significantly increased in those with a BMI higher than 40 mg/m 2 , Monte Carlo simulations predicted excellent stasis target exposure (30% ƒT ≥ MIC) with MIC of 1 mg/L or lower that would be adequate concerning most clinical isolates of Staphylococcus aureus, Streptococcus pneumoniae, and non-extended-spectrum b-lactamaseproducing Escherichia coli or Klebsiella spp. 37 They concluded that higher doses (e.g., every 8 hours) may be considered if targeting 50% fT ≥ MIC for methicillin-resistant S. aureus (MRSA), but this warrants further studies. These results are in line with clinical success reported from retrospective registry data of ceftaroline 600 mg every 12 hours dosing in diabetic foot infections or skin and skin structure infections that included obese patients.…”
Section: Ceftarolinementioning
confidence: 99%
“…Monte Carlo simulations of q12h administration of ceftaroline fosamil conducted by Justo et al using a population PK model developed with data from normal-weight to obese healthy subjects found that in the case of MRSA, the cumulative fractions of response were Ͼ90% for 30% and 40% fTϾMIC targets, and 87.5% was predicted for 50% fTϾMIC (23). The study concluded that the 600 mg q12h regimen was adequate against most clinical isolates; however, more frequent dosing (i.e., q8h) or the use of combination therapy may be more suitable for serious, deep-seated infections due to MRSA.…”
Section: Discussionmentioning
confidence: 99%